2017
DOI: 10.1183/13993003.01296-2016
|View full text |Cite
|
Sign up to set email alerts
|

Randomised comparison of needle aspiration and chest tube drainage in spontaneous pneumothorax

Abstract: Guidelines on spontaneous pneumothorax are contradictory as to intervention between needle aspiration (NA) and chest tube drainage (CTD). Studies show poor adherence to guidelines.Three Norwegian hospitals included patients with primary (PSP) and secondary (SSP) spontaneous pneumothorax. Patients underwent NA or CTD as the primary intervention. The main outcome was duration of hospital stay. Secondary outcomes were immediate- and 1-week success rates and complications.127 patients were included, including 48 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
66
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 35 publications
6
66
1
1
Order By: Relevance
“…Another review of well‐conducted randomized studies published the same year and including results of the largest study in this field by Thelle et al came to the same conclusions . Thelle recently published a randomized controlled study of 127 patients with pneumothorax (79 PSP and 48 SSP) comparing NA with CTD . Median hospital stay was significantly shorter in the NA group (2.4 vs. 4.6 days).…”
Section: Manual Aspiration or Chest Tube Insertion?mentioning
confidence: 73%
See 1 more Smart Citation
“…Another review of well‐conducted randomized studies published the same year and including results of the largest study in this field by Thelle et al came to the same conclusions . Thelle recently published a randomized controlled study of 127 patients with pneumothorax (79 PSP and 48 SSP) comparing NA with CTD . Median hospital stay was significantly shorter in the NA group (2.4 vs. 4.6 days).…”
Section: Manual Aspiration or Chest Tube Insertion?mentioning
confidence: 73%
“…A recent Cochrane systematic review (2017) also reported a shorter hospital stay and a reduction of side effects after simple NA compared to chest tube drainage (CTD) . Another review of well‐conducted randomized studies published the same year and including results of the largest study in this field by Thelle et al came to the same conclusions . Thelle recently published a randomized controlled study of 127 patients with pneumothorax (79 PSP and 48 SSP) comparing NA with CTD .…”
Section: Manual Aspiration or Chest Tube Insertion?mentioning
confidence: 82%
“…In this issue of the European Respiratory Journal, THELLE et al [26] have published a randomised study comparing needle aspiration and CTD in 127 patients with spontaneous pneumothorax. This study is interesting for many reasons.…”
Section: @Erspublicationsmentioning
confidence: 99%
“…In the meantime, the study by THELLE et al [26] is an important one to improve the management of both primary and secondary pneumothorax more conservatively. Every clinician also ought to routinely provide more advice about smoking cessation to reduce the chance of recurrence in patients with a first episode of pneumothorax.…”
Section: @Erspublicationsmentioning
confidence: 99%
“…Thelle et al (16) performed a randomized controlled study comparing needle aspiration NA versus chest tube drainage CTD in patients with spontaneous pneumothorax. A total of 128 patients were included in three Norwegian hospitals including 48 patients with SSP.…”
Section: Editorialmentioning
confidence: 99%